Original paper Test-anxiety in Iranian students: cognitive therapy vs. systematic desensitisation - Fathi-Ashtiani, Ali; Salimi, Seyed Hossein; Emamgholivand, Fatemeh (Archives of Medical Science, 2006)
Introduction: Test anxiety has been regarded as a main school problem. The present research compared the effect of the cognitive therapy (CT) with systematic desensitisation (SD) on reducing test anxiety in high school students. The two main questions of the study were as follows: 1) do the CT and SD reduce test anxiety?, and 2) do these techniques have similar effects on reducing test anxiety or do they reveal significant differences? Material and methods: Sixty students who had higher mean scores on an anxiety questionnaire and without any marked psychological or physical problems were selected from a girls high school as subjects and were divided into three similar groups. The subjects were divided into three matched groups, including two case groups and a control group. The first case group received the cognitive therapy for a period of 12 weeks, while the second one received systematic desensitisation. Results: The results revealed that for both case groups test anxiety mean scores were significantly lower than those for the control group. However, no significant differences were found between the cognitive and desensitisation techniques. Moreover, the effects of both techniques were stable in the three month follow-up period. Conclusions: The results revealed that both psychotherapy techniques have positive and significant effects on reducing the test-anxiety level of students.